Myeloperoxidase–Antineutrophil Cytoplasmic Antibody (ANCA)–Positive Granulomatosis With Polyangiitis (Wegener's) Is a Clinically Distinct Subset of ANCA‐Associated Vasculitis: A Retrospective Analysis of 315 Patients From a German Vasculitis Referral Center. Issue 12 (December 2016) - Schirmer, Jan H.; Wright, Marvin N.; Herrmann, Kristine; Laudien, Martin; Nölle, Bernhard; Reinhold‐Keller, Eva; Bremer, Jan P.; Moosig, Frank; Holle, Julia U.
Abstract : Objective: To compare the phenotype, clinical course, and outcome of myeloperoxidase (MPO)–antineutrophil cytoplasmic antibody (ANCA)–positive granulomatosis with polyangiitis (Wegener's) (GPA) to proteinase 3 (PR3)–ANCA–positive GPA and to MPO‐ANCA–positive microscopic polyangiitis (MPA). Methods: We characterized all MPO–ANCA–positive patients classified as having GPA by the European Medicines Agency algorithm who attended our center, in a retrospective chart review. A second cohort of patients with PR3‐ANCA–positive GPA matched for age and sex was characterized. Patients with MPO‐ANCA–positive MPA from a recently published cohort were also included in the analysis. All patients were diagnosed and treated according to a standardized interdisciplinary approach at a vasculitis referral center. Results: Comprehensive data were available for 59 patients with MPO‐ANCA–positive GPA, and they were compared to 118 patients with PR3‐ANCA–positive GPA and 138 patients with MPO‐ANCA–positive MPA. We observed a distinct phenotype in MPO‐ANCA–positive GPA as compared to the other 2 cohorts. Patients with MPO‐ANCA–positive GPA frequently had limited disease without severe organ involvement, had a high prevalence of subglottic stenosis, and had less need for aggressive immunosuppressive therapy (cyclophosphamide/rituximab). The patients with MPO‐ANCA–positive GPA were also younger than the MPA patients and were predominantly female (significantly different than the MPA cohort). While GPA patients had higher survival rates compared to MPA patients (due to a high prevalence of pulmonary fibrosis in MPA), patients with MPO‐ANCA had significantly lower relapse rates than those with PR3‐ANCA. Conclusion: Patients with MPO‐ANCA−positive GPA show significantly different clinical courses compared to those with PR3‐ANCA−positive GPA or MPO‐ANCA−positive MPA, which should be considered in their clinical management. Classification according to ANCA specificity may improve the evaluation of relapse risk.